2014
DOI: 10.6000/2369-3355.2014.01.01.6
|View full text |Cite
|
Sign up to set email alerts
|

Alumina Surface Treated Pigmentary Titanium Dioxide with Suppressed Photoactivity

Abstract: The aim of the optimization of the technological process was to coat the surface of the pigment in a controlled manner and to supress photoactivity in the titanium dioxide (TiO2) pigment. As part of this research, a systematic approach to TiO2 pigment surface treatment with alumina was conducted. Surface treatment with alumina plays a significant role in the improvement of TiO2 properties (e.g. weather resistance and photostability). This research encompasses a raw material analysis and process conditions stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In such a case, heterogeneous precipitation is Figure 8. At pH higher than the IEP, the number of ─OH groups on the particle surface that could provide protons is large and the condensation with the OH─Al species easily occurs [13]. preferred.…”
Section: Coating Process Of the Al 2 O 3 Layermentioning
confidence: 99%
See 1 more Smart Citation
“…In such a case, heterogeneous precipitation is Figure 8. At pH higher than the IEP, the number of ─OH groups on the particle surface that could provide protons is large and the condensation with the OH─Al species easily occurs [13]. preferred.…”
Section: Coating Process Of the Al 2 O 3 Layermentioning
confidence: 99%
“…However, some of the components can be co-precipitated to alter the pigment characteristics [1]. There are many works regarding this subject in literature [4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…18,19 ROS cause the deterioration of proteins, lipids, and even DNA and disturb cell signaling. 20,21 In previous studies, encapsulating TiO screening effect of TiO 2 NPs and could reduce the generation of ROS, 1,22 conformal surface coating of inert TiO 2 NPs without binding molecules is still challenging. Moreover, it was reported that a high ROS generation level was detected from silica-alumina-coated TiO 2 NPs.…”
Section: Introductionmentioning
confidence: 99%
“…The annual production of inorganic sunscreen agents, such as titanium dioxide and zinc oxide, according to the exposure increment of ultraviolet wavelength to the earth’s surface, has been increasing for decades. 1 , 2 Among those, titanium dioxide nanoparticles (TiO 2 NPs) have been most widely utilized as an ultraviolet wavelength (UV) screening material to prevent photodegradation of various commercial products, including polymers, textile, paint, personal care products, and cosmetics. 1 8 However, the strong aggregation and sedimentation properties make TiO 2 NPs hard to disperse and stabilize in dispersing media with high content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation